From Structure to the Signal (Text and Discourse in the Semiotic Analysis) - مبارك, محمد رضا (ALBAHITH ALALAMI, 2016)
Care and attention to the structure in the sixties of the last century replaced the mark, and if the structure of Ms. pampered in research and studies, it has become the mark is also a spoiled lady .. But the relationship between the structure and the mark was not a break and break, but the relationship of integration, His themes are structural analysis, and these are intellectual themes that can not be surpassed in contemporary research, especially since semiotics have emerged from the linguistic inflection.We have tried to distinguish between text and speech, which is a daunting task, as it seems that whenever the difference between them is clear and clear, we come back to wonder whether the text is the same discourse, and is the speech a set of texts? If so, why should some researchers unite the two terms? ?We have worked as much as we can to try to distinguish between them, using the opinions and theses in this important intellectual polemics, as reaching a clear definition of each of them will be useful in reading the narrative, poetic, and informational motto.We have, of course, used the semiotic approach in analysis, since this research contained two or two parts. The first is a theoretical approach to the analysis method and the second is a practical one. It is related to the analysis of a short historical text, By the Canadian critic Nothrop Frey in expanding the concept of narrative, not limited to specific texts or literary sex, as did the American critic Henry James before. His theory in the narratives became a doctrinal dogma, in particular the definition of conditions or the transfer of arguments that must be followed by the narrator.